Enzima conversora de angiotensina 1 : purificação, imobilização e bioconjugação - Almeida, Fernando Gonçalves de (Universidade Federal de São Carlos, 2015)
Angiotensin converting enzyme 1 (ACE1) is a dipeptidyl carboxypeptidase that converts angiotensin I (decapeptide) to a vasoconstrictor octapeptide angiotensin II. Thus, ACE presents an important role in blood pressure regulation. There are many synthetic commercially available ACE inhibitors such as captopril, lisinopril and enalapril. Due to their side effects, naturally occurring inhibitors have been prospected. In order to endorse this research field we have developed a new tool for ACE ligand screening. To this end, ACE was extracted from bovine lung, purified and chemically immobilized in modified ferrite magnetic beads (ACEMBs). The ACE-MBs have shown a Michaelian kinetic behavior towards hippurylhistidyl- leucine (HHL) and was also able to catalyze the conversion of angiotensin I to angiotensin II. Moreover, as proof of concept, the ACE-MBs was inhibited by lisinopril with an IC50 of 10 nM. At the fishing assay, ACE-MBs were able not only to fish out the reference inhibitor, but also three peptides from a pool of tryptic digested BSA. ACE-MBs emerge as new straightforward tool for ACE kinetics determination, inhibition and binder screening.
Keywords: Enzimas; Cromatografia líquida de alta eficiência; Espectrometria de massa; Atividade enzimática; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA